Syntheses and non-covalent interactions of naphthalene-bearing Schiff base complexes of Zn(II), Co(III), Cu(II) and V(IV): Selective detection of Zn(II). (15th October 2016) - Naskar, Barnali; Modak, Ritwik; Maiti, Dilip K.; Kumar Mandal, Sushil; Kumar Biswas, Jayanta; Kumar Mondal, Tapan; Goswami, Sanchita
Graphical Abstract: Zn(II), Co(III), Cu(II) and V(IV) complexes of a naphthalene bearing Schiff base were synthesized and structurally characterized. The complexes demonstrate a plethora of non-covalent interactions including naphthalene–naphthalene, pyridine–pyridine π–π stacking, nitrate anion⋯π interaction and hydrogen bonding. Selective Zn(II) detection ability was also explored in detail. Abstract: A new Schiff base ligand, 1-[(2-pyridin-2-yl-ethylimino)-methyl]-naphthalen-2-ol, (HPEMN ) has been synthesized equipped with naphthalene and pyridine backbone, to study the interplay of various non-covalent interactions. Experiments have been carried out to investigate the outcome of combinations ofHPEMN and ZnCl2 (1 ), ZnBr2 (2 ), ZnI2 (3 ), Zn(NO3 )2 ·6H2 O (4 ), Co(ClO4 )2 ·6H2 O (5 ), Cu(ClO4 )2 ·6H2 O (6 ) and VO(acac)2 (7 ). The prevalent non-covalent interactions described here include naphthalene–naphthalene (for1, 2, 3 and5 ) and pyridine–pyridine π–π stacking (for4 ) interactions, nitrate anion⋯π interaction (for4 ) and hydrogen bonding (for6 ).HPEMN is able to sense Zn(II) selectively and this phenomenon was further demonstrated by the results of fluorescence studies in H2 O/acetonitrile (8:2, v/v) HEPES buffer (pH = 7.4) solution and human lung cancer cell lines.